(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article presents a brief overview of the work of existing grapple loaders and the results of a kinematic study of the grapple mechanism of a universal loader, substantiation of the parameters of the mechanism that ensure the preservation of the quality of cargo materials and coatings of loading platforms when loading loose lightweight fibrous materials (raw cotton, chicken pile, hay, etc.).